The objects of internal audit management in corporations - Maria Shukhman (Cхід, 2014)
The objects of the Internal Audit Management in corporations are offered and based in the article. Analyzing, systematizing and summarizing scientific labors of many scientists, the types of providing (legal, organizational, informative, methodical, personnel and technical) are defined, the scheme of the internal audit subjects (services) and the internal audit process organization is developed, and a conceptual framework is presented.